Fuel Gas Generation from Gasification of Sacha Inchi Shell using a Drop Tube Reactor. (October 2017) - Lakkhana, Chalatthon; Atong, Duangduen; Sricharoenchaikul, Viboon
Abstract: The optimal fuel gas production conditions for gasification of sacha inchi shell waste were studied with a drop tube reactor. This waste was derived from production of sacha inchi seed oil. Ultimate, proximate and heating value of raw material were analyzed by CHNS/O analyzer, thermogravimetric analysis (TGA) and bomb calorimeter, respectively. Waste particle size was 0.50 - 0.85 mm and the reactor temperature was varied from 700 to 900°C with the equivalent ratio of 0.20 - 0.50. To reduce undesired liquid product, the Ni/dolomite was used as primary catalyst. Solid residue was analyzed for elemental composition while liquid and gas products were analyzed by gas chromatography-mass spectrometry and portable gas analyzer, respectively. It was found that at optimal operating conditions (ER 0.20, 900°C), conversions of carbon to CO, CO2 and CH4 were approximately 30.63%, 14.50% and 6.27%, respectively. Similarly, the conversion of hydrogen to H2 and CH4 were approximately 26.94% and 15.40%, respectively, with the lower heating value at 2.27 MJ/m 3 and cold gas efficiency of gasification process is nearly 40% whereas liquid and solid product were 4.55 % and 34.50%. Apparently, higher temperature had a positive effect on greater gas yield and lower liquid production. Furthermore, catalyst addition reduced liquid proportion and increased potential of CO and H2 production especially for Ni loading of 5% on calcined dolomite. The result showed that conversions of carbon to CO increased to 37.95% and conversion of hydrogen to H2 increased to 34.50%. In addition, liquid and solid production decreased to 2.87% and 14.10%, respectively. The feasibility of incorporating the catalytic process on this particular thermal waste conversion method was discussed.